Expression Regulation and Physiological Role of Transcription Factor FOXO3a During Ovarian Follicular Development - Zhang, Hong; Lin, Fengping; Zhao, Jiuhua; Wang, Zhengchao (Frontiers in Physiology, 2020)
In mammals, developing ovarian follicles transform from primordial follicles to primary follicles, secondary follicles, and mature follicles, accompanied by changes in follicular secretory functions. FoxO3a is a member of the forkhead transcription factor family (FoxO), which plays an important role in the cell cycle, DNA damage repair, apoptosis, oxidative stress, and energy metabolism. Recent studies have shown that FOXO3a is involved in the physiological regulation of follicular development and pathological progression of related ovarian diseases, which will provide useful concepts and strategies for retarding ovarian aging, prolonging the ovarian life span, and treating ovarian diseases. Therefore, the regulation of FOXO3a expression, as well as the physiological contribution during ovarian follicular development are detailed in this paper, presenting an important reference for the further study of ovarian biology.